A Study of E-Banking Implimentation in the Libyan Banking Sector: From Employees Prespective - Nawal Omar, M Towati (2012)
The topic of this paper is relationship between e-banking system and Libyan banks employees:A study in Libya. The main purpose of this study is to investigate the relationship between e-banking system and Libyan banks employees' perspective. This study was conducted among 128 banks in Libya that were listed in Algumhorea website only. The finding obtained from this study indicated that there was a significant, positive relationship between two variables. A positive relationship between e-banking system implementation and Libyan banks employees which lead to reduce transaction cost through e-banking system and make it happened faster.A survey from of this study was considered as questionnaires were distributed among the respondents of this study.The subsequent result shows that all the variables considered are significantly related to e-banking adoption. Recommendations and conclusions are also reported.